(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2020)
An attempt to study the Prospective, observation study was conducted In-patient department of Pulmonology, Siddhartha Multi Speciality Hospital Kakinada, and Andhra Pradesh India. In our study we aim incidence and prevalence of respiratory diseases based up on the study population. The Research study begins with standard questionnaire for collecting patient’s demographic details, diagnosis of the presenting disease condition. The case study was reported for a period of six months and the data obtained from the questionnaires was analyzed in Microsoft excel 2013. In this study strictly followed by inclusion and exclusion criteria, the study was conducted in for six months we conclude most of were interviewed in the study among whom the majority were Males who constituted a count of 57% (n=69) and females constituted 43% (n=51).According to the study, the age group distribution 31- 40 years constituting 27% (n=30) were more affected, followed by 71-80 years constituting 11% (n=15) followed by the rest of the age groups. For the environmental analysis conducted the majority of population affected were found in Rural 70% (n=84), where as urban is 30% (n=36). Daily Wages 38 % (n=45) followed by House Wife’s and students 23% and 17% respectively followed by others such as Employees, farmers. Illiterates mainly affected those who are Daily Wages when compare to the others. COPD is the most Common One 22% (n=28), Followed by Pulmonary KOCHS 13% (n=16) Viral pneumonia 12 %( n=14).